Antara yang Berkuasa dan yang Dikuasai: Refleksi Atas Pemikiran dan Praktek Politik Islam - M. Din Syamsuddin (Al-Jami'ah: Journal of Islamic Studies, 2001)
This article examines the relationship between the ruler and the ruled that are involved and become main factors and actors of socio-political life of a nation. In it, the writer explains the dynamics of political thought and. its consequent deeds in historical process of Islamic civilization both during pre-modem and modem.  Based on his research the writer concludes that there is a gap in the relationship between the ruler and the ruled in the perspective of Islamic political thought and practices. Political reality does not match with the religious ideality. The gap even continues in certain degree and in other form during current modem era.  Therefore, in order to develop modern society often called civil society, government role is very important, namely, to support the development of infra-structural life of community by providing public space in its real meaning. This means that government not only allows its people to speak but also opens its inner eyes for people's aspirations both delivered from formal and non-formal democratic institutions.